Analgesic, anti-inflammatory and sedative/hypnotic effects of Icaritin, and its effect on chloride influx in mouse brain cortical cells - Huang, Fengyu; Zhang, Yaodong; Xu, Yinfeng; Xiang, Wei; Xie, Chaofan (Cellular and Molecular Biology, 2019)
Inflammation and insomnia are medical problems that may severely affect work and health, thereby necessitating strategies for their effective treatment. Icartin (ICT) is a major active monomeric component of icariin . Studies have revealed that ICT possesses several pharmacological properties such anti-inflammatory, anti-tumor, anti-fibrotic, anti-osteoporotic and neuroprotective effects. The present research was carried out to investigate the anti-inflammatory, analgesic and sedative/hypnotic effects of ICT. The results obtained revealed that ICT exerted a good anti-inflammatory effect related to the downregulations of inflammatory cytokines and the inhibition of COX-2 signaling pathway. Moreover, ICT enhanced Cl- influx in mouse cortical cells in a concentration-dependent manner. These data suggest that ICT exerts a hypnotic effect in mice through a mechanism associated with increased Cl- influx in cortical cells.